Strength of pile caps under eccentric loads: Experimental study and review of code provisions. (1st March 2019) - Miguel-Tortola, Lucia; Miguel, Pedro Francisco; Pallarés, Luis
Highlights: 21 tests on four-pile caps eccentrically loaded with different depths and rebar layouts are presented. Most pile caps without vertical reinforcement fail in brittle punching mode. Vertical secondary reinforcement (stirrups) increases the strength and ductility of pile caps. Eccentric loads reduce pile cap strength, but the maximum pile reaction increases. Code provisions safely predict eccentrically loaded pile cap strength, but do not capture the failure mode. Abstract: Pile caps are rigid reinforced concrete structures that transfer column loads, generally consisting of a combination of an axial load and bending moments in one or two directions, to the piles. The design formulations of pile caps for more than two piles were derived from the results of experimental tests under a centered load. The practice of checking both punching and shear failure modes is common as described in the literature review, even though these formulations were developed for more slender elements. Currently, Codes ACI 318-14 and EC2 allow designing pile caps with strut-and-tie models or sectional approaches (shear, punching and flexural designs). In this study, 21 full-scale pile caps with different shear span-depth ratios and reinforcement layouts were studied to investigate the effect of eccentric loading on the strength and accuracy of the code formulations. The results show that in eccentrically loaded pile caps, the ultimate load is reduced but the maximum pile reaction increases and the secondary reinforcement proves effective to enhance the pile cap strength. Although the strut-and-tie models (STM) allow eccentric loads to be taken into consideration, they predict a much lower peak load than that observed at the experimental results and do not adequately reflect either the influence of slenderness or the failure mode. In general the sectional approach provided by Codes ACI-318-14, EC2 and MC-2010 (Level I of Approximation) lead to safe predictions of the peak load but do not always correctly predict the failure mode. The ultimate load predicted by EC-2 formulation comes closest to the experimental peak load, accurately reflects the influence of slenderness and the effect of secondary reinforcement, however, additional assumptions need to be made for its application. The ACI formulation complemented by the CRSI-2008 Special Investigation for deep pile caps is the safest but does not adequately capture the effect of horizontal and vertical secondary reinforcement. The MC2010 LoAI formulation is also conservative but does not detect the influence of slenderness or the contribution of secondary reinforcement.